Masthead - Regina Hoffman (Patient Safety, 2019)
ABOUT PATIENT SAFETY As the journal of the Patient Safety Authority, committed to the vision of “safe healthcare for all patients,” Patient Safety (ISSN 2689-0143) is fully open access and highlights original research, advanced analytics, and hot topics in healthcare.